2005
DOI: 10.4088/pcc.v07n0103
|View full text |Cite
|
Sign up to set email alerts
|

Practical Clues to Early Recognition of Bipolar Disorder

Abstract: Early treatment can favorably impact the course of bipolar disorder, a lifelong illness. Because bipolar disorder can masquerade as various mental and physical illnesses-primarily major depressive disorder-patients with this condition frequently go unrecognized for years. During this recognition lag, such patients may present to their primary care physician on multiple occasions. Accordingly, primary care physicians would benefit from knowing the "clues" to early recognition of the disorder, because early reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 77 publications
0
28
0
1
Order By: Relevance
“…Por todo lo mencionado, no existe mucha evidencia de que la hipersomnia y el aumento de apetito sean síntomas que pertenezcan al síndrome depresivo, aun cuando parecen ser relevantes como indicadores de bipolaridad (19)(20)(21)(22). Asimismo, la presencia de características atípicas en un episodio depresivo se asocia con comorbilidad psiquiátrica de diverso tipo incluyendo trastornos de ansiedad (especialmente fobia social), por uso de sustancias, de personalidad (exceptuando el tipo antisocial), psicosis e intentos suicidas (23).…”
Section: Discussionunclassified
“…Por todo lo mencionado, no existe mucha evidencia de que la hipersomnia y el aumento de apetito sean síntomas que pertenezcan al síndrome depresivo, aun cuando parecen ser relevantes como indicadores de bipolaridad (19)(20)(21)(22). Asimismo, la presencia de características atípicas en un episodio depresivo se asocia con comorbilidad psiquiátrica de diverso tipo incluyendo trastornos de ansiedad (especialmente fobia social), por uso de sustancias, de personalidad (exceptuando el tipo antisocial), psicosis e intentos suicidas (23).…”
Section: Discussionunclassified
“…BD is a mental disorder that is manifested by mood alterations, characterized by episodic mood swings (mania or depression) (Swann et al, 2005). Schizophrenia is a mental illness characterized by the so-called 'positive' symptoms, that include hallucinations and delusions and 'negative' symptoms contributing to the social and occupational dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In one primary care practice, those with a lifetime history of bipolar disorder were significantly more likely than those without bipolar disorder to have current symptoms of anorexia or overeating, low self-esteem, suicidal ideation, alcohol use, and a history of hallucinations. 12 Mitchell et al 19,20 systematically reviewed the literature and found that the clinical symptoms of hypersomnia, hyperphagia, leaden paralysis, psychomotor retardation, psychotic features, pathological guilt, mood lability and longer speech latency occurred more often in bipolar depression than in unipolar depression ( Table 2).…”
Section: Strategies To Improve Recognition In Individualsmentioning
confidence: 99%